Relation between Iliopsoas cross-sectional area and kicked ball speed in soccer players - Wakahara, T.; Chiba, M. (International Journal of Sports Medicine, 2018)
This study aimed to investigate the relationship between the maximal anatomical cross-sectional area (ACSA) of the iliopsoas muscle and ball speed in side-foot and instep kicks. The ACSA of the psoas major and iliacus was measured in 29 male collegiate soccer players by using magnetic resonance imaging. They performed maximal side-foot and instep kicks to a stationary ball. The kicked ball speed was measured with a high-speed camera. Ball speed in the side-foot and instep kicks was significantly correlated with body height (side-foot kick: r=0.650, P<0.001; instep kick: r=0.583, P<0.001). After adjustment for body height, the maximal ACSA of the psoas major was significantly correlated with ball speed in the side-foot kick (r=0.441, P=0.017), but not in the instep kick. The maximal ACSA of the iliacus was not correlated with ball speed in side-foot or instep kicks, even after adjustment for body height. Our results suggest that: 1) body height is a significant determinant of the ball speed in side-foot and instep kicks, and 2) for a given body height, the maximal ACSA of the dominant psoas major is a factor that affects the ball speed in side-foot kick.